Repositioning an Immunomodulatory Drug Vidofludimus as a Farnesoid X Receptor Modulator With Therapeutic Effects on NAFLD - Zhu, Yanlin; Xu, Shuangshuang; Lu, Yi; Wei, Yijuan; Yao, Benqiang; Guo, Fusheng; Zheng, Xing; Wang, Yumeng; He, Ying; Jin, Lihua; Li, Yong (Frontiers in Pharmacology, 2020)
Non-alcoholic fatty liver disease (NAFLD) has become the most common chronic liver disorder, and yet with no pharmacological treatment approved worldwide. The repositioning of old drugs provides a safe approach for drug development. Vidofludimus, an inhibitor for dihydroorotate dehydrogenase (DHODH) for the treatment of autoimmune disorders, is herein uncovered as a novel modulator for farnesoid X receptor (FXR) by biochemical and crystallographic analysis. We further revealed that vidofludimus exerts in vivo therapeutic effects on dextran sodium sulfate (DSS)-induced colitis in an FXR-dependent manner. Notably, vidofludimus also possesses remarkable beneficial effects in reducing NAFLD by targeting FXR, which may represent a unique approach in developing the treatment for NAFLD. Our findings not only reveal a promising template for the design of novel FXR ligands in treating autoimmune disorders, but also uncover a novel therapeutic effect for vidofludimus on NAFLD based on the newly established relationships among drugs, targets, and diseases.